Pengaruh Penggunaan Metode Presentasi (Advance Organizer) Terhadap Hasil Belajar Kelas X Di MA DA Jerowaru - Muhamad Zaril Gapari (Al-Gafari : Manajemen dan Pendidikan, 2023)
Study results or achievements is realization or expansion from skills potential or existing capacity someone. A student said own mastery results Study can seen from Act in demand child. Study This aim For know influence method presentation (advance organizer) to results Study class X MA DA Jerowaru. Study This is study experiment. With population whole student class X MA DA Jerowaru consists of 4 (four) classes. Taking sample done with technique cluster random sampling that is taking two classes in a manner random and placed class Xa as class experiments and class Xb as class control, group experiment given application method presentation (advanced organizer) meanwhile class control No given. Results data Study student obtained with use test. Collected data Then analyzed with use technique analysis statistics, the formula used is Based t-test formula results data analysis obtained t- count of 64.67 and the t- table value is 1.708 at the level significant 5% with dk 25 of 1.708, p the shows t- count more big from t- table (64.67 > 1.708). With thereby can concluded that method presentation (advanced organizer) effect positive and significant to results Study class X MA DA Jerowaru.